Evaluation of The Government's Internal Quality Control System in the Implementation of Good Governance - Warni Tune Sumar; Asni Ilham; Besse Marhawati (Green Publisher Indonesia, 2022)
Evaluation of the government's internal quality control system (SPIP) in the implementation of good governance at the Gorontalo district regent's office. In order to realize quality internal control of government quality, an evaluation of the implementation and internal quality is carried out through research. The method used in this research is descriptive quantitative evaluation of the research sample totaling 31 regional employees. Data collection techniques are questionnaires, observations and documents. The data in the study were analyzed by the percentage formula (%). The research results show that. (1). Evaluation of the government's internal quality control system (SPIP) in the implementation of good governance with control environment indicators is in the less effective category with a percentage of 69,93%. (2). Evaluation of the government's internal quality control system (SPIP) in the implementation of good governance with risk assessment indicators is in the less effective category with a percentage of 68.01% (3). Evaluation of the government's internal quality control system (SPIP) in the implementation of good governance with indicators of control activities in the effective category with a percentage of 70.48%. (4). Evaluation of the government's internal quality control system (SPIP) in the implementation of good governance with indicators of information and communication is in the effective category with a percentage of 74.19%, (5). evaluation of the government's internal quality control system (SPIP) in the implementation of good governance with indicators of monitoring and internal control is in the less effective category with a percentage of 68.81%.